The Africa Gender Innovation Lab’s Core Empowerment Indicators : Developing a Cross-Country Module to Complement Context-Specific Measures - Donald, Aletheia; Goldstein, Markus (World Bank, Washington, DC, 2020)
To advance economic gender equality in Africa, the authors first need to know which development programs work to economically empower women. Better data on gender-informed development indicators is imperative for tracking the progress in promoting gender equality, designing interventions to address gender-based constraints and rigorously evaluating their impact. Measurement of women’s economic empowerment requires a clear conceptualization of what empowerment is and is not. One guiding definition that the authors use at the Africa gender innovation lab (GIL) is economic empowerment as the ability and power to generate income and accumulate assets, and to control their disposition. Beyond being clear on what is being measured, how it is measured also matters - and selecting the best tools for the task is no easy feat. In impact evaluations, tailoring measurement to reflect local economic arrangements and capture the specific pathway the project is intending to affect can yield a more precise (and useful) picture of women’s economic empowerment. On the other hand, systematically tracking the same indicators across projects can provide a broader understanding of the relationship between intermediate and final empowerment outcomes, as well as between different empowerment domains, such as assets, mobility, time, attitudes, and aspirations. Moreover, practitioners and policymakers have emphasized the need for a concise set of practical metrics that can be easily shared and used.